FORMULASI DAN AKTIVITAS ANTIOKSIDAN SERUM KOMBINASI KELOR DAN TELANG - Kharismatunnisa Lestari; Muhammad Nurul Fadel; Galih Kurniawan (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Free radicals play a crucial role in the development of premature aging and degenerative diseases, thereby necessitating the use of antioxidants to mitigate oxidative damage. Moringa oleifera Lam. leaves and Clitoria ternatea L. flowers are recognized as natural sources of antioxidants with strong activity and potential synergistic effects. This study aimed to formulate a stable facial serum containing a combination of Moringa oleifera and Clitoria ternatea extracts and to determine the formulation exhibiting optimal antioxidant activity. An experimental laboratory approach was employed by preparing serum formulations with varying extract ratios, followed by evaluations of physical stability and antioxidant activity using the DPPH method. The results demonstrated that all serum formulations remained homogeneous before and after the cycling test. Physical parameters, including pH, spreadability, and viscosity, exhibited changes during stability testing but remained within acceptable ranges for serum preparations. The IC₅₀ values indicated strong antioxidant activity for formulations F1, F2, and F3, weak activity for the negative control, and very strong activity for the positive control. Among the combination formulas, the serum containing a 1:1 extract ratio showed the highest antioxidant activity. In conclusion, the combined extract serum of Moringa oleifera and Clitoria ternatea demonstrated good physical and chemical stability, with optimal antioxidant potential observed in the 1:1 formulation.